Understanding proximity in the Baltic languages: Latvian relational adverbs blakus and līdzās and their Lithuanian counterparts - Žilinskaitė-Šinkūnienė, Eglė; Šķilters, Jurģis (Baltistica, 2022)
This article aims to clarify the difference in usage of the Latvian proximity lexemes blakus and līdzās and to identify their translation equivalents in Lithuanian. The data have been collected from the Lithuanian-Latvian and Latvian-Lithuanian parallel corpus, manually annotated for various syntactic and semantic variables, and analyzed quantitatively. Although Latvian relational adverbs blakus and līdzās are defined very similarly in Latvian dictionaries, our results reveal their syntactic and semantic peculiarities in more detail and outline the criteria that sanction the choice of these relational adverbs. Finally, the translation of Latvian proximity terms into Lithuanian is described emphasizing the main differences of proximal terms in both languages.